Learning technology and organisations: transformational impact? - Martin Hall; Mike Keppell; John Bourne (Association for Learning Technology, 2010)
This collection of papers contributes to a wide and ongoing strand of interest in alternative learning technologies: how are digitally-enabled ways of working transforming organisations? In ‘transformation' we look for radical change, rather than just doing the same at a different scale. And in organisations we centre on educational institutions – across the full range of schooling, training, further and higher education – while recognising that conventional boundaries are increasingly broken as different kinds of organisations invest in digitally-enabled learning.